2022
DOI: 10.1111/eip.13344
|View full text |Cite
|
Sign up to set email alerts
|

Housing trajectories and the risk of homelessness among new mental health service users: Protocol for the AMONT study

Abstract: Aims High rates of mental illness among individuals experiencing homelessness, as well as documented contacts with psychiatric services prior to episodes of homelessness, indicate that early intervention could play a key role in homelessness prevention. Decision‐makers and clinical teams need longitudinal data on housing trajectories following initial contact with psychiatric services, as well as on predictors of risk of housing instability and homelessness. This paper describes the AMONT study, a mixed‐method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…A comprehensive description of the overall study methodology and methods can be found in the published protocol (Roy et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive description of the overall study methodology and methods can be found in the published protocol (Roy et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…They occur during a critical period of life, specifically in late adolescence and early adulthood (Birchwood, 2014). Their consequences include an increased rate of suicide and acts of violence (Fu et al, 2021; Sicotte et al, 2021; Whiting et al, 2021), low employment rates (Plana‐Ripoll et al, 2023), reduced life expectancy by 15 years (Laursen et al, 2014; Romain et al, 2021), as well as homelessness and experiences of stigmatization (Deschênes et al, 2021; Roy et al, 2022). In Canada, the economic burden of these conditions was estimated to be $7 billion in 2004 while the global estimates indicate a range between 0.02% and 1.65% of the gross domestic product in 2016 (Chong et al, 2016; Goeree et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They occur during a critical period of life, specifically in late adolescence and early adulthood [2]. Their consequences include an increased rate of suicide and acts of violence [3][4][5], low employment rates [6], reduced life expectancy by 15 years [7,8], as well as homelessness and experiences of stigmatization [9,10]. In Canada, the economic burden of these conditions was estimated to be $7 billion in 2004 while the global estimates indicate a range between 0.02% and 1.65% of the gross domestic product in 2016 [11,12].…”
Section: Introductionmentioning
confidence: 99%